Utilization of Family Medicinal Plants (TOGA) for Hypertension Prevention in Bontopanno Hamlet - Dian Ihwana; Arranury, Zilfadhilah; Lagu, Abd Majid HR; Rachmat, Alya Fatihah; Muzakinah, Syabila (Unihealth Community Research, 2026)
Hypertension is a non-communicable disease whose prevalence continues to increase and remains a major risk factor for cardiovascular diseases such as stroke and coronary heart disease. Limited public knowledge regarding risk factors and preventive measures constitutes a significant barrier to hypertension control efforts. This study aimed to evaluate the effectiveness of an educational intervention in improving community knowledge regarding the utilization of family medicinal plants (Tanaman Obat Keluarga / TOGA) as an alternative approach to hypertension prevention. The intervention employed lectures, pamphlets, and group discussions and involved 31 respondents. The results demonstrated a significant increase in participants’ knowledge regarding hypertension prevention through TOGA utilization following the intervention, with a p-value of 0.000. These findings highlight the important role of health education in strengthening non-communicable disease prevention efforts and improving overall community health status.